Impact of Gender-confirming Chest Surgery on Sexual Health: A Prospective Study - Camille de Schoulepnikoff, MMed; Olivier Bauquis, MD, MER, EBOPRAS; Pietro G. di Summa, MD, PhD, EBOPRAS, FMH (Plast.) (Plastic and Reconstructive Surgery, Global Open)
Background:. Few studies have evaluated the improvement of the sexual well-being of transgender patients after breast augmentation or bilateral mastectomy. This prospective study aims to assess the potential improvement in body awareness during sexual intercourse, as well as the nipple-areolar complex (NAC) sensitivity recovery after gender-confirming chest surgery. Methods:. From October 2019 up to April 2021, all transgender patients eligible for gender-confirming chest surgery in our institution were asked to fill out two questionnaires, namely BREAST-Q (a patient-reported outcome measure for use in reconstructive breast surgery and clinical practice) and Body Exposure during Sexual Activities Questionnaire (scientifically validated self-report assessments of body-image experiences in the context of sexual relations). The Semmes-Weinstein monofilament test was used to evaluate NAC sensitivity recovery. Different follow-ups were considered: preoperative and 4 and 12 months postoperative. Results:. Twenty-one transmasculine and 12 transfeminine patients met the inclusion criteria. For both groups, the preliminary 4-month postoperative evaluations showed significant improvement in psychological well-being and chest/breast satisfaction compared with preoperative values. Body awareness during sexual intercourse improved significantly at 4 months postoperative in the transmasculine groups (P ≤ 0.001) and at 12 months postoperative in the transfeminine group (P ≤ 0.01). No correlation between body awareness during sexual intercourse and NAC sensitivity was observed among either group, transmasculine and transfeminine patients. Conclusions:. Although aesthetic and psychological well-being increased quickly postoperatively, sexual health remained low among transfeminine patients until they completed their transition with vaginoplasty. NAC sensitivity recovery was found to not contribute to the improvement of the sexual health of transgender patients.